Cytoreductive robot‐assisted prostatectomy for systemic prostate rhabdomyosarcoma presenting as urinary retention. Issue 2 (29th December 2021) - Kirisawa, Takahiro; Fukunaga, Arinobu; Takamori, Hajime; Maejima, Aiko; Shinoda, Yasuo; Komiyama, Motokiyo; Fujimoto, Hiroyuki; Yonemori, Kan; Yoshida, Akihiko; Matsui, Yoshiyuki
Abstract : Introduction: In adults, rhabdomyosarcoma of the prostate is extremely rare and has an unfavorable prognosis. These patients frequently experience urinary obstruction, and cysto‐prostatectomy is a mainstay treatment for localized disease. In contrast, treatment strategies for the primary site for metastatic disease remain controversial. To our knowledge, robot‐assisted surgery for the primary tumor has not been reported. Case presentation: A 26‐year‐old man complained of dysuria. Magnetic resonance imaging showed enlarged prostate and computed tomography revealed a pulmonary metastasis. Transurethral resection of the prostate led to the diagnosis of rhabdomyosarcoma. After chemotherapy, robot‐assisted prostatectomy was performed to relieve obstructive urinary symptoms. Although disease progression in the metastatic site was observed after the surgery, urinary obstruction did not occur and quality of life was well maintained. Conclusion: Robot‐assisted prostatectomy may be beneficial both for local disease control and palliation of voiding impairment among selected patients with systemic rhabdomyosarcoma of the prostate.